2017
DOI: 10.1038/srep46192
|View full text |Cite
|
Sign up to set email alerts
|

Response of the North Atlantic surface and intermediate ocean structure to climate warming of MIS 11

Abstract: Investigating past interglacial climates not only help to understand how the climate system operates in general, it also forms a vital basis for climate predictions. We reconstructed vertical stratification changes in temperature and salinity in the North Atlantic for a period some 400 ka ago (MIS11), an interglacial time analogue of a future climate. As inferred from a unique set of biogeochemical, geochemical, and faunal data, the internal upper ocean stratification across MIS 11 shows distinct depth-depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 61 publications
1
25
0
Order By: Relevance
“…McManus et al (1999) first showed at ODP Site 980 in the subpolar North Atlantic Ocean that significant suborbital variability over the last 500 ka occurred when ice sheets reached a critical size. This variability was later confirmed by Helmke and Bauch (2003), , and Kandiano et al (2016) for the Nordic seas and in midlatitudes of the northeast North Atlantic by Voelker et al (2010), Rodrigues et al (2011), Doherty and Thibodeau (2018), and Kandiano et al (2017). Figure 4 shows several of these proxy records for the period MIS 12 through MIS 10 (450 to 350 ka) going from north (top, panel 4a) to south (bottom, panel 4j).…”
Section: Paleoceanography and Paleoclimatologymentioning
confidence: 76%
See 1 more Smart Citation
“…McManus et al (1999) first showed at ODP Site 980 in the subpolar North Atlantic Ocean that significant suborbital variability over the last 500 ka occurred when ice sheets reached a critical size. This variability was later confirmed by Helmke and Bauch (2003), , and Kandiano et al (2016) for the Nordic seas and in midlatitudes of the northeast North Atlantic by Voelker et al (2010), Rodrigues et al (2011), Doherty and Thibodeau (2018), and Kandiano et al (2017). Figure 4 shows several of these proxy records for the period MIS 12 through MIS 10 (450 to 350 ka) going from north (top, panel 4a) to south (bottom, panel 4j).…”
Section: Paleoceanography and Paleoclimatologymentioning
confidence: 76%
“…Taken together, these records show that suborbital variability linked to glacial processes and ocean circulation were fundamental features both during Termination V and the MIS 11‐10 transition in regions of the Nordic seas and North Atlantic. Transient suborbital cold events during Termination V were likely triggered by freshwater influx from melting ice, perhaps the Greenland Ice Sheet, and they affected surface, middepth, and deeper water layers as well as the AMOC (Kandiano et al, ). Similarly, during the transition into the MIS 10 glacial starting about 395 ka, there were multiple cool/warm cycles reflecting a weakening AMOC similar to those seen in HE during the MIS 5a‐MIS 3 interval (Voelker et al, ).…”
Section: The Mis 11 Interglacialmentioning
confidence: 99%
“…This hypothesis seems to be supported by investigations performed with other organisms: for example, the cis-12 linoleate isomerase (LAI) gene of Fusarium graminearum (FgLAI12), responsible for the conversion of LA into RA, was characterized (32). Assays of gene deletion mutants showed, among other effects, a reduction of mycelial growth.…”
Section: Cfa and Rumen Biohydrogenationmentioning
confidence: 86%
“…Two additional abrupt cold events have also been recognized in MIS 11 by a high-resolution lacustrine record from North Asia (Prokopenko et al, 2010). Furthermore, a temperature record from the North Atlantic (Kandiano et al, 2017) Figures 4 and S9). Notably, the YXEs show average pacing of~1.4 Kyr and amplitude of~0.8‰ (Table S3 and Figure S9), which broadly resembles the Holocene WMEs inferred by the counterpart cave records (Dykoski et al, 2005;Wang, 2005).…”
Section: Asm Events During the Holocene In The Context Of Mis 11cmentioning
confidence: 77%